Spatial Orientation in the Immediate Environment: How Can the Different Theories be Reconciled? - Riecke, B.E.; McNamara, T. P (10. Tübingen Perception Conference (TWK), 2007)
Recently, there has been an increasing interest in theories about human spatial memory and orientation (see, e.g., Burgess, 2006 for a recent review). There is, however, an apparent conflict between many of those theories that yet needs to be re-solved. Here, we outline a theoretical framework that aims at integrating two current theories of spatial orientation: May (2004) pro-posed that the difficulty of imagined perspective switches is caused, at least in part, by an interference between the sensori-motor and the to-be-imagined perspectives. Riecke & von der Heyde (2002) developed a theoretical framework that is based on a network of logical propositions (i.e., necessary and sufficient conditions). They proposed that automatic spatial updating can only occur if there is a consistency between the observer's concurrent egocentric reference frames (e.g., mediated by real world perception, virtual reality [VR], or imagined perspectives). We propose that the underlying processes are the same, in the sense that a consistency between egocentric representations (Riecke & von der Heyde, 2002) is equivalent to an absence of interference (May, 2004). Whenever the current egocentric representations of the immediate surroundings are consistent, there should be no interference. According to Riecke & von der Heyde (2002), this state enables automatic spatial updating. We propose that this lack of interference might also be able to explain other important phenomena, such as the relative ease of adopting a new perspective after being disoriented. Con-versely, interference (inconsistency) between the primary, embodied egocentric representation and a to-be-imagined (e.g., experimentally instructed) egocentric representation implies the difficulty of adopting a new perspective. We posit that such interference or inconsistency also explains the difficulty people have in ignoring bodily rotations. To avoid the vagueness that purely verbally defined theories sometimes suffer from, we offer a well-defined graphical and structural representation of our framework. Integrating logical and information flow representations in one coherent frame-work not only provides a unified representation of previously seemingly isolated findings and theories, but also fosters a deeper understanding of the underlying processes and enables clear, testable predictions. [1] Burgess, N. (2006): Trends in Cognitive Sciences 10(12), 551-557 [2] May, M. (2004): Cognitive Psychology 48(2), 163-206 [3] Riecke, B. E. and von der Heyde, M. (2002): TR 100, MPI for Biological Cybernetics. Avaliable: www.kyb.mpg.de/publication.html?publ=2021 NIMH Grant 2-R01-MH57868. TWK 2007
Keywords: Riecke; Riecke_2007; bernhard-riecke; egocentric; frame; framework; iSpaceWeb; interference; model; orientation; reference; spatial; talkWithoutPaper; theory; timothy-mcnamara; updating